Developing a Data Analysis and Visualization Educational Decision Support System (EDSS) - Silva, Edeilson Ferreira da (My University, 2024)
Institutional language providers are constantly seeking to deliver better experience for its students, a movement that fosters implementation of different technologies with focus on this industry. Following literature, to accomplish this objective any designed strategy must involve a comprehensive way to deal with its historical data. The quality of its generated data will allow institutions to see what happened in the past, understand the current situation and make informed decisions for future improvements. Conjecture that encourages the development of an Educational Decision Support System (EDSS). To create it, a Systematic Literature Review was carried out to understand the trends in digital solutions for the educational management field, followed by consistent methodology. Methodology Design Science Research (DSR) was the path to respond to this class of problem by building a satisfactory solution with pragmatic validity. The result shows that EDSS can lead educational institutions to embrace data culture, adopt data governance and consequently get more quality. It also reveals the system was easy to operate but with room for improvement regarding data update rate.

Instituições de ensino de idiomas estão constantemente buscando oferecer a melhor experiência para seus estudantes, movimento que promove a implementação de diferentes tecnologias com foco neste setor. Na literatura, para atingir este objetivo, qualquer estratégia projetada deve envolver uma maneira abrangente de lidar com seus dados históricos e na qualidade deste ativo, isso permitirá uma visão consistente do passado, compreensão do presente e fundamento para decisões futuras. Conjuntura que motivou o desenvolvimento de um Sistema de Suporte à Decisão Educacional (EDSS). Para criá-lo, foi realizada uma Revisão Sistemática da Literatura para entender as tendências em soluções digitais para o campo da gestão educacional, seguida de metodologia consistente. A metodologia Design Science Research (DSR) foi o caminho para responder a esta classe de problema construindo uma solução satisfatória com validade pragmática. Os resultados mostram que o EDSS pode levar as instituições educacionais a abraçar a cultura de dados, adotar a governança de dados e, consequentemente, garantir a qualidade na aquisição dos dados, que é base para tomada de decisões. Além disso, revela que o sistema era fácil de operar, mas com espaço para melhorias em relação à taxa de atualização de dados.
Keywords: Academic management; Data-informed decision making; Educational decision support system (EDSS); English language provider; Institutional administration; Administração institucional; Gestão acadêmica; Provedor de língua inglesa; Sistema de suporte à decisão educacional (EDSS); Tomada de decisão baseada em dados